Effect of northwestern photoperiod and exogenous melatonin on the psychoemotional state of the Syrian hamsters (Mesocricetus auratus) - E. P. Antonova; I. V. Baishnikova; A. G. Kizhina; V. A. Ilyukha (Acta Biomedica Scientifica)
Background. Among the environmental factors that influence the increase in the frequency of occurrence of psychoemotional states, great importance is attributed to the light conditions. However, the mechanisms of behaviour regulation in the mammals in non-standard light conditions and the role of melatonin in this process have not been fully studied.The aim of the study. To assess the effects of specific northern light conditions and melatonin on the behavior of Mesocricetus auratus.Methods. The animals were divided into 4 groups: LD (control), NL (northern light conditions), and LD + mel and NL + mel (melatonin, 100 μg/animal). The study of behavioral reactions, the level of emotional and phobic anxiety state of animals was carried out in the “Open field” and “Dark chamber with holes” installations.Results. Keeping M. auratus in NL had a negative effect on their behavior – a decrease in motor activity (horizontal and vertical) and the “hole-exploratory behavior”, an increase in the number of freezing and grooming reactions and the time of the first peeking out of the upper hole were revealed. It was shown that melatonin contributed to an increase in exploratory activity and a decrease in the number of anxiety acts in NL + mel group compared to NL group; the opposite effect of the hormone on these parameters was observed in LD + mel group.Conclusion. The obtained results indicate the important role of photoperiod and melatonin in regulating the behavior of seasonally breeding species.